Pendidikan Kewarganegaraan : Analisis Atas Paham Nasionalisme dan Konsep Persatuan - Dismas Kwirinus; Valentinus Saeng (Universitas Muhammadiyah Makassar, 2023)
The focus of this research is to examine civic education by analyzing the notion of nationalism and the concept of unity based on Sila III of Pancasila in the Preamble of the 1945 Constitution. The topic of study relates to issues of nationalism and unity which are frequently discussed. For example, the expression for the sake of national unity and integrity is echoed everywhere, specifically for the stability of national security, it is also discussed in official meetings of state officials, in books and magazines, both scientific and non-scientific. The researcher uses descriptive qualitative methods and critical reading of the text, namely: (1) the 1945 Constitution; (2) Books related to the notion of nationalism and the concept of national unity; (3) Articles that concentrate on studying the concept of national unity based on Sila III Pancasila and the Preamble to the 1945 Constitution. The findings in this study are that the concept of nationalism and the concept of unity is based on Sila III Pancasila and the Preamble to the 1945 Constitution, the notion of unity here means that the state protects all the Indonesian nation and all of Indonesia's bloodshed is based on unity and the realization of social justice for all six people. The definition of a unified state is that the state overcomes all group understandings, individual understandings, wants unity to cover the entire Indonesian nation. The state and every civil society prioritizes the interests of the state above the interests of certain groups or individuals.